Scottish Churches, Morality and Homosexual Law Reform, 1957-1980 - Meek, Jeffrey (The journal of ecclesiastical history, 2015)
The role of Scottish Churches in the decision not to include Scotland in the 1967 Sexual Offences Act requires scrutiny. This article examines the role of the Church of Scotland, and other Churches, in debates regarding homosexuality in the years following publication of the Wolfenden Report. It argues that although Scotland's Churches appeared steadfast in their determination to prevent homosexual law reform during the 1950s and 1960s, there was much ambivalence, contradiction and debate and that, in fact, Scotland's two main Churches played a significant role in the development of Scotland's foremost homosexual rights organisation, the Scottish Minorities Group.